The Silent Sequelae: Irreversible Profound Sensorineural Hearing Loss Following Mumps Parotitis in a Pediatric Patient - I Made Wiranadha; Ni Putu Oktaviani Rinika Pranitasari; I Gede Wahyu Adi Raditya; Janris Sitompul (Archives of The Medicine and Case Reports, 2026)
Mumps-associated Sudden Sensorineural Hearing Loss (SSNHL) is a rare but catastrophic complication of epidemic parotitis, historically estimated to occur in 1 per 20,000 cases. Despite global vaccination efforts, the re-emergence of mumps in adolescent populations due to waning immunity poses significant otologic risks. This report documents a case of unilateral, profound SSNHL in a vaccinated pediatric patient, highlighting the diagnostic challenges when auditory symptoms manifest after the resolution of systemic parotitis. An 11-year-old Balinese male presented with acute-onset tinnitus and hearing loss in the left ear, occurring one week after the clinical resolution of bilateral parotid swelling. The patient had a history of basic immunization. Audiometric evaluation revealed profound sensorineural hearing loss in the left ear with a Pure Tone Average of 110 dB, while the right ear remained normal. Serological analysis confirmed acute mumps infection with a highly positive IgM titer (Index 11.0). Hematological profiling demonstrated leukopenia with a neutrophil shift. Despite a prompt and aggressive multimodal treatment protocol including high-dose intravenous methylprednisolone, oxygen therapy, and neurotrophic support, follow-up audiometry at 14 days revealed no functional improvement (Pure Tone Average 91.25 dB). In conclusion, mumps-induced SSNHL is characterized by rapid, irreversible cochlear destruction that frequently exhibits resistance to corticosteroid therapy. The dissociation between the resolution of systemic parotitis and the onset of otologic sequelae requires high clinical vigilance. This case emphasizes the critical need for serological confirmation in pediatric SSNHL and underscores the poor prognosis associated with this specific viral etiology.